Propuesta de creación de una incubadora de negocios dirigida al sector gastronómico en la ciudad de Ibarra. - Mantilla, Jeny E. (2022)
This research is aimed to develop a business incubator for the foodservice industry in Ibarra, Ecuador. This incubator will contribute to sustainability of start-ups, considering that today there are no business incubators in this city. Through this incubator entrepreneurs will be able to access a fully equipped workspace and a network of mentors who will provide efficient technical support at all stages of incubation. These strategies are intended both to reduce bad decision making and to improve sustainability of new ventures. At a methodological level, a census was carried out on students of the Gastronomy career of the Catholic University of Ibarra. Results show that 70% of respondents pretend to start a new business in the foodservice industry after completing their university career. However, 93.4% of people do not know about incubators. This data supports the importance of generating this incubator, as it will constitute an alternative to support the sustainability and profitability of new ventures in the foodservice industry.